Zemahşerî’nin El-Keşşâf’ında temsili anlatım - Sağdıç, Sedat (My University, 2017)
Bu çalışmanın ana konusu, Zemahşerî’nin Keşşâf isimli tefsirindeki “temsîl” yaklaşımıdır. Çalışmanın ilk bölümünde Arap dili belâgatı açısından temsîl teriminin anlamı tespit edilmeye çalışılmıştır. Çalışmanın ikinci ve üçüncü bölümlerinde ise seçilen bazı ayetler üzerinden Zemahşerî’nin temsîl anlayışı belirlenmiştir. Örnek olarak ele alınan ayetlerin incelenmesi sonucunda, Zemahşerî’nin -birçok araştırmacının iddiasının aksine- temsîl yaklaşımının tek gayesinin mezhebî kaygılar olmadığı anlaşılmıştır.

The main subject of this study is the representation approach in the exegesis called Kashsaaf Zamakhshari. In the first chapter of the study, the meaning of the representation concept is tried to be determined by referring to sources of the classical Arab language. In the second and third chapters of the study, Zemahsherî’s representation approach has been determined through some selected verses. As a result of examining the verses which have been dealt with as an example, it has been understood that main purpose of Zamakhshari’s representation approach is not doctrinal concerns contrary to the claims of many researches.
Keywords: (Quranic Exegesis) Zamakhshari; Hermeneutics; Islam; İslam; Kashsaaf; Keşşâf Representation; Mecaz; Metaphor; Tafseer; Tefsir; Temsîl; Zemâhşerî